Inhibiting microglia exacerbates the early effects of cuprizone in males in a rat model of multiple sclerosis, with no effect in females - Xavier, Soniya; Younesi, Simin; Sominsky, Luba; Spencer, Sarah J. (Frontiers in Neurology, 2023)
Hyper-activity of the brain’s innate immune cells, microglia, is a hallmark of multiple sclerosis (MS). However, it is not clear whether this involvement of microglia is beneficial or detrimental or whether manipulating microglial activity may be therapeutic. We investigated if inhibiting microglial activity with minocycline prevents the early changes in oligodendrocyte and myelin-related markers associated with a demyelinating challenge in adult female and male rats. Cuprizone reduced the expression of myelin and oligodendrocyte genes in both females and males, reflective of cuprizone intoxication and the early phases demyelination, and reduced the number of oligodendrocytes in the corpus callosum. However, we see notable differences in the role for microglia in this response between females and males. In males, myelin and oligodendrocyte genes, as well as oligodendrocytes were also reduced by minocycline treatment; an effect that was not seen in females. In males, but not females, early changes in oligodendrocyte and myelin-related genes were associated with microglial proliferation in corpus callosum, and this increase was reversed by minocycline. These data indicate sex-specific effects of inhibiting microglia on the early changes leading to demyelination in an MS model and suggest microglia may play a key role in myelin stability in males but not in females. This highlights a strong need for sex-specific understanding of disease development in MS and suggest that treatments targeting microglia may be more effective in males than in females due to differing mechanisms of disease progression.